The Effectiveness of a Problem-Based Learning Model Based on Banten Culture in Improving the Critical Thinking Skills of Social Sciences Class VI Students at Elementary School 1 Rangkasbitung Timur - Usmaedi; Puji Siswanto; Jumyadi, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Critical thinking skills are one of the important abilities today, so the teacher's role is needed during the learning process to be able to provide stimulus by using creative and innovative learning models. Thus, this research aims to determine: 1) the level of effectiveness of the Banten culture-based problem-based learning model in improving the social studies critical thinking skills of grade VI students at elementary school 1 Rangkasbitung Timur. 2) determine the increase in social studies critical thinking skills of grade VI students at elementary school 1 Rangkasbitung Timur after using a problem-based learning model based on Banten culture. This research employes a quasi-experimental design with a sampling technique using saturated samples. The research instrument used was a test instrument in the form of essay questions with a total of 8 questions. The results of the Gregory content validity test are worth 1, which means the question is very valid and the results of the Cronbach alpha reliability test are 0.688 > 0.60, which indicate that the questions are reliable. The data analysis techniques used are initial prerequisite testing and hypothesis testing. The results obtained in this research are as follows: 1) based on the independent t-test, namely 0.000 < 0.05, which means Ho is rejected and Ha is accepted so it can be concluded that the Banten culture-based problem-based learning model is effective in improving students' social studies critical thinking skills class VI at elementary school 1 Rangkasbitung Timur. 2) based on the results of the paired t-test, namely 0.000<0.05, which means that there is an increase in the social studies critical thinking skills of class VI students at elementary school 1 Rangkasbitung Timur after using the problem-based learning model based on Banten culture, it is also strengthened with the results of the N-gain test analysis of 0.3294 with an increase in the medium category.